Strategi Pembekalan Memasuki Dunia Kerja: Integrasi Self-Marketing, Proses Seleksi, dan Kesiapan Profesional - Mislan Sihite; Elperida J. Sinurat; Junika Napitupulu; Robinhot Gultom; Rintan Saragih; Jeudi A. T. P. Sianturi; Jamaluddin Jamaluddin; Jon H. Purba; Siti Normi; Kristanty M. N. Nadapdap; Mangasa Panjaitan; Tiur Rajagukguk; Selamat Siregar; Henri Saragih (Universitas Methodist Indonesia, 2026)
The transition from higher education to employment requires multidimensional readiness, including technical competence, interpersonal skills, psychological maturity, and professional self-presentation. This community service activity aims to provide systematic career preparation training for final-year students through self-marketing strategies, recruitment selection understanding, job application preparation, and interview readiness. The implementation method consisted of lectures, simulations, and interactive discussions. The results showed that participants gained increased understanding of recruitment processes, improved confidence, and awareness of professional ethics. The activity concluded that structured career preparation significantly improves graduate employability and professional readiness in entering the labor market.